Strategies and delivery systems for cell-based therapy in autoimmunity - Matteo Puccetti; Claudio Costantini; Aurélie Schoubben; Stefano Giovagnoli; Maurizio Ricci (Frontiers Media S.A., 2024)
This review article explores the potential of engineering antigen-presenting cells (APCs) for the immunotherapy of autoimmune diseases. It discusses various strategies for modifying APCs to induce antigen-specific tolerance, thereby mitigating autoimmune responses. The review covers recent advancements in APC engineering techniques, including genetic modification and nanoparticle-based approaches, and evaluates their efficacy in preclinical models and clinical trials. Additionally, challenges and future directions for the development of APC-based immunotherapies for autoimmunity - and other forms of cell-based immunotherapy - are discussed. Along this direction, this review (i) describes various strategies for engineering APCs, including genetic modification, nanoparticle delivery systems, and ex vivo manipulation techniques; (ii) discusses the selection of target antigens and the design of APC-based immunotherapies, and (iii) reviews preclinical models used to evaluate the efficacy and safety of engineered APCs in inducing antigen-specific tolerance.